Sinkretisme Budaya Jawa dan Islam dalam Gamitan Seni Tradisional Janengan - Wawan Hernawan; Tatang Zakaria; Aini Rohmah (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this research is to explore the practice of syncretism in Janengan traditional art in Kesugihan Village, Cilacap, Central Java. This study employs a qualitative research with a multi-disciplinary approach contained four historical method stages. The result of the research shows that Janengan traditional art in Kesugihan Village Cilacap is known as salawat Janengan or salawat illau. It contains Islamic teachings about faith and tasawuf (Islamic mysticism) combined with Javanese local cultural patterns. The community perform this traditional art in slametan events, especially at the commemoration of the Prophet's Birthday (Maulid Nabi Saw.). In conclusion, the syncretism of Javanese-Islamic culture in syi’ir or salawat singir with the Javanese genre as well as sajen (offerings) in each of these arts is strong. This study recommends conducting policy research in strengthening the preservation of Javanese-Islamic traditional arts and Indonesian contexts.